Characteristics of coseismic responses of groundwater level in Jiaji well, China - Yang Liu; Fan Zhang; Huamei Zhang; Xiaojing Xie; Sheng Li (Geomatics, Natural Hazards & Risk)
Jiaji well exhibits a sudden rise-decline coseismic response to earthquakes of Mw7.5 or above. Based on the amplitude and phase of the tidal response of the well-water level, the short-term post-seismic step change alternates between upward and downward movement, owing to a change in permeability in the seepage aquifer. This analysis reveals that the seismic wave can create new fissures in the seepage aquifer. It may also block fissures within the aquifer by causing them to collapse, changing the tidal factor and phase of the well-aquifer system. The tidal factor and phase of the aquifer system, and their parameters, can recover with time during the non-seismic cycle. These damage-recovery processes are directly related to the bedrock lithology being a sandy conglomerate. The simultaneous rise in the well-water level and its temperature anomaly in August 2017 was caused by lowered permeability in the aquifer. The installation site of the water temperature sensor was in a semi-pressurized aquifer, where the low temperature of the shallow layer was recharged by the high temperature of the underlying layer.